Laser-induced-fluorescence measurement of thermal conductivity in warm dense matter generated by pulsed-power discharge - Sasaki, Toru; Sugimoto, Satoshi; Sugimoto, Yuki; Watabe, Arata; Kusano, Shingo; Takahashi, Kazumasa; Kikuchi, Takashi; Harada, Nobuhiro (21st International Symposium on Heavy Ion Inertial Fusion. Autonomous Organization of Education “Nazarbayev University”, 2016)
Thermal conductivity in warm dense matter is one of the interests for thermonuclear fusion scenarios. Alternative inertial confinement fusion, which is a fast ignition with applied magnetic field [1], has been considered to improve the coupling efficiency. The target behavior of the fast ignition with applied magnetic field depends on the anisotropic thermal conductivity. The magnetic confinement fusion (MCF) [2] Up to now, the heat load on the divertor in previous MCF systems has been unreached parameter. Thus, to predict properties of the divertor under these heat loads, several experiments have been performed using several methods[3-6]. To predict the performance of the tungsten divertor in MCF, we should analyze not only metallurgical properties but also thermophysical properties of ablated tungsten...
Keywords: laser-induced-fluorescence measurement; thermal conductivity; magnetic fusion